Exploring the impact of corporate entrepreneurship on organizational performance in the ICT companies of Jordan: The moderating role of gender-diverse leadership - AbuKaraki, Abdullah Aref Mahfouz; Fawehinmi, Olawole; Salleh, Hayatul Safrah; Abdullah, Abdul Hafaz Ngah (Asian Development Policy Review, 2024)
This study focuses on addressing challenges faced by Jordanian Information and Communication Technology (ICT) organizations, aiming to explore solutions for sector sustainability amid troubling economic conditions. Specifically, it investigates the impacts of Corporate Entrepreneurship (CE) and Top Management Team Gender Diversity (TMTGD) on the performance of these organizations. Furthermore, it also examines the moderating role of TMTGD within this context. To achieve these objectives, the study collects data from 300 employees considered part of the top management teams within Jordan's ICT sector. Utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM), the study estimated both measurement and structural models to thoroughly examine the data and proposed relationships. The findings indicate that CE and TMTGD have positive and statistically significant effects on organizational performance. However, the study also uncovers a nuanced pattern of interaction between these variables. Explicitly, it suggests that the presence of gender diversity within top management teams may attenuate the otherwise positive impact of CE on organizational performance. Hence, this research suggests that ICT companies should actively cultivate a corporate entrepreneurship culture to elevate their organizational performance. Furthermore, policymakers and leaders are encouraged to initiate training and educational programs addressing gender dynamics and biases with the goal of fostering a more inclusive and equitable workplace.